Complex processing of lipids from liver of the gonatid squid Berryteuthis magister - Ekaterina V. Ermolenko; Ruslan M. Sultanov; Sergey P. Kasyanov; Yury G. Blinov (Известия ТИНРО)
Berryteuthis magister is one of the most common commercial species in the North-West Pacific, but its liver never was utilized before, though it was a rich source of the lipids with simple ether links, 1- О -alkyl-glycerol ethers (АGE), and ω3 polyunsaturated fatty acids (ω3 PUFA). Technology for complex processing of lipids from its liver is developed and presented in details. These forms of lipids are distinguished by a wide range of biologic activity: AGE are effective immunomodulators which enhance hemopoiesis, relieve lesions and lower risk of secondary lesions under radio-therapy and can be used for treatment of some malignant tumors (glioma, prostate cancer, lung carcinoma, etc.); ω3 PUFA could be used for prophylactic of cardiovascular diseases, Alzheimer’s sclerosis, senile dementia, skin diseases (protein synthesis control) and other diseases. The presented technology provides extraction of three preparations with different chemical composition and pharmacological activity. Both saturated and unsaturated AGE could be extracted using the property of different solubility in organic solvents for different components of the mixture of hydrolyzed lipids. The main component of the saturated AGE fraction is chimyl alcohol (90.5 %), but the unsaturated fraction contains 54.7 % of monounsaturated AGE. The ω3 PUFA are concentrated to summary 46 % content of eicosapentaenoic acid and docosahexaenoic acid by the method of fatty acids crystallization with carbamide. Comparing with traditional raw materials for АGE and ω3 PUFA production, as shark liver, the liver of gonatid squid is more suitable because of its high and accessible resources, whereas sharks are presented in bycatch only so cannot be considered as a stable source.